The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1002/(sici)1097-0185(199807)251:3<384::aid-ar14>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of blood vessels in the rat incisor pulp: A scanning electron microscopic and immunoelectron microscopic study

Abstract: Although two types of nerve endings have been proposed to innervate blood vessels in the dental pulp, the precise innervation pattern is not well understood. This is mainly due to the lack of information regarding the positional relationships of nerve fibers with blood vessels at the electron microscopic level.The rat incisor pulp was investigated by scanning electron microscopy (SEM) after connective tissue digestion and by transmission electron microscopy after immunohistochemical localization with polyclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…The mouse incisor is innervated by sensory and sympathetic nerves (Ishizuka and Hiura, 1992; Johansson et al, 1992; Tabata et al, 1998; Zhang et al, 1998) but is devoid of parasympathetic nerves (Olgart, 1996; Sasano et al, 1995). Nerve fibers accompanying the arteries are located within the periarterial region, which is similar to the tunica adventitia of free arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse incisor is innervated by sensory and sympathetic nerves (Ishizuka and Hiura, 1992; Johansson et al, 1992; Tabata et al, 1998; Zhang et al, 1998) but is devoid of parasympathetic nerves (Olgart, 1996; Sasano et al, 1995). Nerve fibers accompanying the arteries are located within the periarterial region, which is similar to the tunica adventitia of free arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The avidin‐biotin complex (ABC) visualization method was reported in our previous study (Tabata et al, 1998). Briefly, the circumvallate papillae were put into a solution containing 0.1% glutaraldehyde and 4% paraformaldehyde in a phosphate buffer for 4 h on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria can invade dentinal tubules, but do not invade dentine because of the outward movement of dentinal fluid that contains immunoglobulins. 21 Thus, coronal dentine may have weak defences against bacteria and noxious agents penetrating into dentinal tubules. Previous studies reported that a higher rate of dentinal fluid flow may induce a larger stress on mechanoreceptors, resulting in an elevated intradental nerve firing rate.…”
Section: Discussionmentioning
confidence: 99%